On the diversity of the genus Spiophanes Grube, 1860 (Annelida: Spionidae) in the Spanish peninsular coast, with descriptions of two new species - Delgado-Blas, Victor Hugo; Díaz-Díaz, Oscar; Viéitez Martín, José M. (Cahiers de Biologie Marine, 2019)
The study of the polychaetes belonging to the genus Spiophanes Grube, 1860, collected from several coastal locations around the Spanish coast, revealed the presence of two new species, Spiophanes convexus sp. nov. and Spiophanes pulchram sp. nov. Also, the type material of Spiophanes afer Meißner, 2005 is revised and redescribed, and the presence of Spiophanes bombyx (Claparède, 1870) is confirmed although several specimens remain doubtfull and named as S. cf. bombyx. Spiophanes convexus sp. nov. and S. pulchram sp. nov. are characterized by the shape of the anterior margin of the prostomium and the distribution of the dorsal ciliated organs, as well as the presence of dorsal membranous crests on the mid-posterior chaetigers. Spiophanes cf. bombyx is characterized by its very long anterolateral horns, and the specific patterning of the dorsal ciliated organs: a pair of short, oblique segmental ciliated bands at about chaetiger 4, and metameric L-shaped ciliated bands after chaetiger 10 to about chaetiger 14 which become increasingly oblique in their orientation. A key for all Spiophanes species known from the Spanish coastline is provided.
World Polychaeta Database (WPolyDb). post-hoc ZooBank registration. No ZooBank prior registration indication in the article. Cahiers de Biologie Marine is online only from volume 59.